The Implementation of Character Education in the English Teaching Learning Using 2013 Curriculum - Thoyyibah, Naelatut; Hartono, Rudi; Anggani L. Bharati, Dwi (Universitas Negeri Semarang, 2019)
The present study is caused by Juvenile delinquency and the problem of moral deficiency of young generations nowadays. The character building is recently much needed in Indonesian education as a way to overcome those problems because strengthening personal and social of morality is one of the fundamental aims of life and moral education is one of important aspects of education. The Ministry of Education (MOE) of the Republic of Indonesia is implementing its new curriculum named 2013 Curriculum. One of the ultimate goals of this new curriculum is to improve the moral and character of the students. This study was aimed to describe how the teachers implement character education in English teaching learning process at SMP N 1 Kebonagung Demak. The data were obtained by conducting a document study, observations and interviews. The subject of this research were two English teachers in SMP N 1 Kebonagung as purposive sampling who taught in the classroom observed to get the data about implementation of character education in learning process classroom. This study revealed that teachers had implemented some character values in the teaching learning process. The most frequent was religiousness, honesty, discipline, perseverance/hard work, independence, democracy, curiosity, achievement respect, responsibility, communicative competence of character values into their teaching learning process. Moreover, the implementation of character education gives teachers with several advantages and challenges in teaching process.